Cell-free DNA profiles of dermatomyositis and its potential role in discriminating phenotypes - Tang, Zhuang-li; Chen, Peng-yu; Zhang, Heng; Cao, Hua-li; Dai, Ru; Lou, Yu-chen; Sun, Yan-hong; Zhou, Yuan; Chen, Xue-yan; Zhang, Mei-jie; Wang, Ya-qi; Man, Xiao-yong (Frontiers in Immunology, 2025)
BackgroundCell-free DNA (cfDNA) functions in the early-detection and monitoring of autoimmune diseases including systemic lupus erythematosus and rheumatoid arthritis. However, investigations into cfDNA profiles in dermatomyositis and their potential clinical implications remain scarce.ObjectivesTo explore the overall landscape of cfDNA profiles in dermatomyositis and investigate potential roles in discriminating subtypes.MethodsFollowing informed consent, 24 treatment-naïve patients diagnosed with dermatomyositis and 16 healthy controls were enrolled. We examined cfDNA concentrations, fragment distribution patterns, 5’-end motif frequencies and genetic variation profiles in all participants and studied potential correlation with laboratory parameters. Moreover, intergroup differences of cfDNA profiles among patients and potential correlation between extracellular DNases levels and cfDNA were investigated.ResultsCompared to healthy controls, dermatomyositis patients exhibited elevated cfDNA concentrations, with significantly longer cfDNA fragments, primarily centered around 180–360 bp; nonetheless, no correlation was witnessed between lab parameters and cfDNA levels. The A-end predominated the 5’-end motif, whereas the C-end was underrepresented, contrasting with the patterns observed in healthy controls. In addition, genetic variations in several genes, including PDE4DIP and BRCA2, were commonly detected in cfDNA from dermatomyositis patients. Notably, end-motif profiles and cfDNA fragment length exhibited variations between anti-transcription intermediary factor 1-gamma positive patients with and without malignancies. However, owing to limited sample size, we failed to draw conclusions regarding extracellular DNase levels.ConclusionsThis study presents the first comprehensive depiction of cfDNA profiles in patients with dermatomyositis. Furthermore, cfDNA features exhibit variability across some sub-phenotypes and may serve as discriminatory indices. Finally, potential involvement of extracellular DNases in cfDNA profiles in dermatomyositis shall be further investigated.